COVID-19 Lockdown Home Gardening in the Western Province of Sri Lanka - Perera, T.G.U.P; Wickramaarachchi, N.C; Karunarathne, H.M.L.P; Munasinghe, L.M; Rupasinghe, K (Journal of Social Sciences and Humanities Review, 2021)
Sampling a set of households from three districts of the Western Province, this paper explored the landscape of lockdown home gardening which took place during the first wave of the COVID-19 pandemic in Sri Lanka. A structured questionnaire published online enabled collecting 939 household responses. A descriptive analysis performed using the IBM SPSS package highlights that the lockdown conditions have intensified the level of home gardening of the participants. The study validates the findings from recent studies that home gardening has no dividing line when it comes to the socioeconomic character of households. Primary benefit of home gardening is of households’ being in seek of good and healthy consumption, vegetables and fruits have been the most preferred crop types to grow. Application of organic fertiliser have been preferred by the majority of the households. This study supports the notion that urban land scarcity is not a limiting factor for home gardening. The paper suggests that this home gardening trend reignited during the Covid-19 lockdown needs to be supported by three means: promoting healthy lifestyles, connecting government officials with local home gardeners and local plans being supportive and appreciative of home gardening.
Keywords: Lockdown Home Gardening, COVID-19, Urban Agriculture, Gardener Engagement, Benefits, Challenges, Sri Lanka